Role of Mathematical Competencies in Enhancing Students’ Academic Performance in Physics in Port Harcourt Local Government Area Rivers State - Doris, Omeodu M. (European Scientific Journal, ESJ, 2019)
The study investigated ‘‘Role of Mathematical Competencies in Enhancing Students’ academic Performance in Physics in Port Harcourt Local Government Area Rivers State’’. The study specifically sought to determine; the mathematical competencies of Physics students, the mean score of students with high mathematical competencies (HMC), medium mathematical competencies (MMC), and low mathematical competencies (LMC) in Physics, and also the mean difference that exists between the performance of students with HMC, MMC and LMC in Physics. The study adopted correlation design. The total number of S.S.3 science students in these four schools was 76 students but due to certain circumstances during the time of the study, only 62 of the students were present and used in the study. The instrument used in the study was mathematics achievement test and physics achievement test. In MCT, students who scored 40 below were grouped as those who have low mathematical competencies, those who scored 41-69 were grouped as medium mathematical competencies while those who score 70 above were grouped as those with high mathematical competencies. Both tests were score and analyzed using mean and standard deviation. The hypothesis was tested using Pearson Product Moment Correlation Coefficient PPMC at 0.05 level of significance. The study found that 22.58 %of respondents haveHMC, 30.65% has MMC and majority of them has LMC 46.77%. The study also found that students with HMC performed significantly better than those with MMC and LMC in Physics tests. The hypothesis confirmed that there was a strong positive correlation between mathematical competency and performance in physics. The researcher therefore recommends that science students should strive hard to be adequately competent in subjects involving abstract logical reasoning and numeric calculations as this may enhance their overall academic performance.